Adsorption of Azo Dye Acid Red 73 onto Rice Wine Lees: Adsorption Kinetics and Isotherms - Qian Wang; Liping Liang; Fenfen Xi; Gangliang Tian; Qiaole Mao; Xu Meng (Advances in Materials Science and Engineering)
The adsorption properties of rice wine lees for acid red 73 in aqueous solution were studied in order to explore the recyclability of rice wine lees and to solve the pollution of dye-contaminated wastewater. Hence, the azo dye acid red 73 was selected as the model pollutant. Effects of parameters including pH, rice wine lees dosage, and initial concentration of acid red 73 on the adsorption activity were investigated to determine the optimal conditions for removal of acid red 73. The experimental results showed that acid red 73 removal by rice wine lees decreased with increasing pH and initial concentration of acid red 73 and increased with increasing rice wine lees dosage. The adsorption reaction was consistent with pseudo-first-order kinetic models, and the adsorption process was physisorption. The adsorption isotherm could be described well with the Freundlich equation, and the maximum adsorption capacity was 18.74 mg·g−1.